Cloning, nucleotide sequence, and expression of the chromate resistance determinant of Pseudomonas aeruginosa plasmid pUM505. - Cervantes, C (1990)
The chromate resistance determinant of Pseudomonas aeruginosa plasmid pUM505 was cloned into broad-host-range vector pSUP104. The hybrid plasmid containing an 11.1-kilobase insert conferred chromate resistance and reduced uptake of chromate in P. aeruginosa PAO1. Resistance to chromate was not expressed in Escherichia coli. Contiguous 1.6- and 6.3-kilobase HindIII fragments from this plasmid hybridized to pUM505 but not to P. aeruginosa chromosomal DNA and only weakly to chromate resistance plasmids pLHB1 and pMG6. Further subcloning produced a plasmid with an insert of 2,145 base pairs, which was sequenced. Analysis of deletions revealed that a single open reading frame was sufficient to determine chromate resistance. This open reading frame encodes a highly hydrophobic polypeptide, ChrA, of 416 amino acid residues that appeared to be expressed in E. coli under control of the T7 promoter. No significant homology was found between ChrA and proteins in the amino acid sequence libraries, but 29% amino acid identity was found with the ChrA amino acid sequence for another chromate resistance determinant sequenced in this laboratory from an Alcaligenes eutrophus plasmid (A. Nies, D. Nies, and S. Silver, submitted for publication).